2005
DOI: 10.1073/pnas.0507454102
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+regulatory T cells limit the risk of autoimmune disease arising from T cell receptor crossreactivity

Abstract: The molecular-mimicry theory proposes that immune crossreactivity between microbial and self-antigen is the initiating event in the activation of autoaggressive immune responses leading to autoimmune disease. In support of this possibility, it is now accepted that T cell recognition of antigen is highly degenerate. However, it is to be expected that the immune system would have evolved mechanisms to counter such a potential danger. We studied the influence of CD4 ؉ CD25 ؉ regulatory T cells (Treg) on the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
1
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 33 publications
7
83
1
1
Order By: Relevance
“…Our findings are consistent with the observation that anti-CD25 antibodies do not mediate FOXP3 expression in CD4 + CD25 − T cells [37]. However, the data presented here vary from the absence of compensatory expansion of CD25 − FOXP3 + T cells in response to anti-CD25 antibodies in a model of experimental autoimmune encephalomyelitis in wild-type mice [38]. Since anti-CD25 antibodies do not always deplete CD25 + T cells [27], but rather inhibit their function [37], the cytokine environment might be less favourable for expansion of the CD25 − FOXP3 + T cells [39].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with the observation that anti-CD25 antibodies do not mediate FOXP3 expression in CD4 + CD25 − T cells [37]. However, the data presented here vary from the absence of compensatory expansion of CD25 − FOXP3 + T cells in response to anti-CD25 antibodies in a model of experimental autoimmune encephalomyelitis in wild-type mice [38]. Since anti-CD25 antibodies do not always deplete CD25 + T cells [27], but rather inhibit their function [37], the cytokine environment might be less favourable for expansion of the CD25 − FOXP3 + T cells [39].…”
Section: Discussionsupporting
confidence: 92%
“…1 also [17]). In contrast to the original hypothesis, our data and several others [15,[17][18][19][20][21] have shown that PC61 mAb treatment does not completely remove Foxp3 1 Treg. In peripheral blood, $30% of Foxp3 1 Treg with low or no CD25 expression remain untouched by PC61 mAb (Fig.…”
contrasting
confidence: 99%
“…In peripheral blood, $30% of Foxp3 1 Treg with low or no CD25 expression remain untouched by PC61 mAb (Fig. 1 also [17,19,21]). Nevertheless, the fact that PC61 mAb treatment elicits such a profound effect on immune responses indicates that partial elimination of Foxp3 1 Treg is sufficient to disrupt immunological balance between the regulators and the effectors.…”
Section: Treg Depletion By Pc61 Mabmentioning
confidence: 92%
“…However, the adoptive transfer of MUC1-expanded CD4 ϩ CD25 Ϫ T cells from WT mice to MUC1-Tg mice to raise the level of MUC1-specific T cell help is a proof of principle that we believe can be applied to the clinic where patients would receive transfers of autologous Treg-depleted Th cells that are expanded to large numbers in vitro by stimulation with MUC1. Restoring the balance to the MUC1-specific immune response via the provision of a defined component, such as functional Th cells, may be a more feasible clinical approach to treating malignancies than global depletion of the patients' Tregs, which may be fraught with side effects such as autoimmunity (55)(56)(57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%